2020
DOI: 10.1016/j.heliyon.2020.e05235
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion, economic growth, and poverty alleviation: evidence from eastern Indonesia

Abstract: The need for a good understanding of the relationship between financial inclusion and economic growth has become a significant concern in national development. Both sectors play an essential role in formulating income distribution policies and reducing poverty, evidence from Eastern Indonesia. This paper, therefore, empirically analyzes the contribution of the financial inclusion to economic growth, poverty alleviation and income inequality in Eastern Indonesia. The Toda-Yamamoto VAR bivariate causality model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
93
2
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 52 publications
13
93
2
11
Order By: Relevance
“…The answers to these questions only represent the usage dimension of financial inclusion, which represents how well the people of one particular household know about finance. Many factors influence this financial awareness, and the dominant factors are the level of education and the subtlety of financial services [ 58 , 59 ]. Moreover, financial inclusion is a broad concept, and as such, it requires multidimensional assessments [ 60 , 61 ].…”
Section: Methodology and Datamentioning
confidence: 99%
“…The answers to these questions only represent the usage dimension of financial inclusion, which represents how well the people of one particular household know about finance. Many factors influence this financial awareness, and the dominant factors are the level of education and the subtlety of financial services [ 58 , 59 ]. Moreover, financial inclusion is a broad concept, and as such, it requires multidimensional assessments [ 60 , 61 ].…”
Section: Methodology and Datamentioning
confidence: 99%
“…The empirical results indicated that financial inclusion reduces income inequality but has no impact on poverty in the MENA region. Erlando et al (2020) discussed how financial inclusion contributes to economic growth and the reduction of poverty in Indonesia using the vector autoregression model (VAR) and the panel vector autoregression model (PVAR). The results showed a two-way causality between financial inclusion, economic growth and poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although substantial reductions in poverty have taken place in Indonesia (Muryani & Esquivias, 2021;Purwono et al, 2021;Yusuf & Sumner, 2015), the Gini ratio (a measure of income or wealth inequality within a nation) has deteriorated over the past two decades (van Leeuwen & Földvári, 2016). Inequality in the country remains substantially significant (Erlando et al, 2020). Government efforts to promote more rapid economic growth, attract more FDI, and create more sophisticated jobs have been more active than ever (Das & Sethi, 2020;Esquivias & Harianto, 2020).…”
Section: Introductionmentioning
confidence: 99%